(untitled) (Research, Society and Development, 2024)
Introduction: Obstructive sleep apnea is characterized by obstruction of the airways and inspiratory flow during sleep, and is now recognized as a risk factor for the development of hypertension. Objectives: This study aims to review contemporary and multidisciplinary approaches to the diagnosis and treatment of the correlation between obstructive sleep apnea and hypertension, highlighting recent advances and scientific gaps. Materials and Methods: This is an integrative literature review on the general clinical characteristics of arterial hypertension secondary to obstructive sleep apnea. The PICO strategy was used to develop the guiding question. In addition, the descriptors “Obstructive Sleep Apnea”; “Hypertension”; “Treatment” were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: It was possible to find strong evidence to explain the emergence of hypertension as a result of obstructive sleep apnea. Conclusion: Hypertension secondary to obstructive sleep apnea (OSA) occurs due to airway obstruction during sleep, leading to episodes of hypoxemia, which activate the sympathetic nervous system and increase blood pressure. This condition is often resistant to conventional treatment and is associated with an increased risk of cardiovascular complications. Appropriate treatment of OSA, such as the use of CPAP, is essential for effective control.